Coronary artery bypass grafting is associated with immunoparalysis of monocytes and dendritic cells. Issue 8 (17th March 2020) - Perros, Alexis J.; Esguerra‐Lallen, Arlanna; Rooks, Kelly; Chong, Fenny; Engkilde‐Pedersen, Sanne; Faddy, Helen M.; Hewlett, Elise; Naidoo, Rishendran; Tung, John‐Paul; Fraser, John F.; Tesar, Peter; Ziegenfuss, Marc; et al.
Abstract: Coronary artery bypass grafting (CABG) triggers a systemic inflammatory response that may contribute to adverse outcomes. Dendritic cells (DC) and monocytes are immunoregulatory cells potentially affected by CABG, contributing to an altered immune state. This study investigated changes in DC and monocyte responses in CABG patients at 5 time‐points: admission, peri‐operative, ICU, day 3 and day 5. Whole blood from 49 CABG patients was used in an ex vivo whole blood culture model to prospectively assess DC and monocyte responses. Lipopolysaccharide (LPS) was added in parallel to model responses to an infectious complication. Co‐stimulatory and adhesion molecule expression and intracellular mediator production was measured by flow cytometry. CABG modulated monocyte and DC responses. In addition, DC and monocytes were immunoparalysed, evidenced by failure of co‐stimulatory and adhesion molecules (eg HLA‐DR), and intracellular mediators (eg IL‐6) to respond to LPS stimulation. DC and monocyte modulation was associated with prolonged ICU length of stay and post‐operative atrial fibrillation. DC and monocyte cytokine production did not recover by day 5 post‐surgery. This study provides evidence that CABG modulates DC and monocyte responses. Using an ex vivo model to assess immune competency of CABG patients may help identify biomarkers to predict adverse outcomes.